DIGITAL NOMADISM IN BULGARIA: RETHINKING SOCIAL IDENTITY ANDCULTURAL BOUNDARIES IN THE GLOBAL ERA - Petrova, Yoana; Petrov, Daniel (E-Journal VFU, 2024)
In the digital age, characterized by technological innovations and globalization, digital nomadism rethinks the traditional notions of identity and belonging. The study examines the influence of modern infrastructure, economic accessibility, and intercultural communication on both professional and personal development. Interviews with representatives from various sectors underscore that this phenomenon integrates the local with the global, forming new social networks and hybrid identities that respond to the challenges of today’s social context.